Multi-scale analysis of urban sprawl in Europe: Towards a European de-sprawling strategy. (December 2015) - Hennig, Ernest I.; Schwick, Christian; Soukup, Tomáš; Orlitová, Erika; Kienast, Felix; Jaeger, Jochen A.G.
Abstract : Graphical abstract: Abstract : Highlights: Increasing urban sprawl in Europe causes land-use conflicts and threatens sustainable land use. Monitoring of urban sprawl is needed to guide European policy development. We measure urban sprawl at the scales of countries, NUTS-2 regions, and 1-km 2 grid. We identify the regions of highest and lowest levels of urban sprawl. We propose a European de-sprawling strategy, including targets and limits. Abstract: Urban sprawl is a major challenge on the way to sustainable land use as highlighted by the International Year of Soils 2015. Because of increasing awareness of this threat in Europe, there is an urgent need to monitor urban sprawl and to guide European policy development. We found considerable sprawl in Europe at three scales with highly affected regions in the centre and along the Mediterranean coast using recently available consistent data across Europe from the European Copernicus programme. Based on our results, we propose a European de-sprawling strategy, including the implementation of targets and limits, and a set of concrete measures to control urban sprawl and to use land in a more resource-efficient way.